Generating a reference model of the surface with a hole for downstream process. Issue 4 (3rd July 2016) - Silayi, Gulibaha; Kinoshita, Tsutomu; Matsuyama, Katsutsugu; Konno, Kouichi
ABSTRACT: The value of 3D CAD models is continuously increasing in downstream processes. The more extensive use of a 3D model outside traditional design and manufacturing is trending now. To distribute 3D data quickly to downstream departments is significant boosts to product quality, production costs, and delivery to markets. Unfortunately, interoperability causes poor communication since downstream applications rely on the reusability and interoperability of CAD models. However, 3D CAD data size for expressing precise forms tends to be big and time-consuming for computation, which may interfere in the communication. In addition, downstream processes emphasize surface smoothness more than precision. Therefore, this paper describes the reconstruction method of a smooth surface by integrating the advantages of Gregory and B-spline surfaces. In this paper, a new surface representation is proposed. Two surfaces are connected with G 1 -continuity by using the control points at the common boundary obtained from joining equations. The internal control point that is not connected to the boundary curve is obtained from the least squares approximation method. The proposed method is applicable to shapes with a hole. GRAPHICAL ABSTRACT: